Dada a função , tem como f (x)=![\frac{x^{2}- 5x +6 }{(x - 2)} \frac{x^{2}- 5x +6 }{(x - 2)}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D-+5x+%2B6+%7D%7B%28x+-+2%29%7D)
zero da função
a 2
b 2 e 3
c 3
d 5
e 6
Soluções para a tarefa
Respondido por
0
seja a função:
f(x) = (x² - 5x + 6)/(x - 2)
fatoração:
(x - 2) * (x - 3)/(x - 2) = 0
x -- 3 = 0
x = 3 (C)
x = 2 não é uma raiz por causa da divisão
Mat2016:
Obrigado!
Perguntas interessantes
Lógica,
10 meses atrás
Matemática,
10 meses atrás
Inglês,
10 meses atrás
Administração,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás